Negative pressure pulmonary edema: a case report - Xiong, Jun (BMC Anesthesiol, 2019)
BACKGROUND: The negative pressure pulmonary edema is rare clinical situation which caused mainly by upper airway obstruction. However except upper airway obstruction, there may be other pathophysiological disorders making patients more vulnerable to pulmonary edema. Based on these disorders, upper airway obstruction is the trigger to induce negative pressure pulmonary edema. CASE PRESENTATION: This case was a 5-year-old girl with tumor on saddle area, her hormones level were abnormal preoperatively, such as cortisol, adrenocorticotrophic hormone, free T4 and total T4. During the stage of induction, negative pressure pulmonary edema took place due to mild upper airway obstruction. And the instant chest Computer tomography proved diagnosis clue. After intensive care, most lung field of this girl recovered to normal within 48 h. CONCLUSION: The patient with abnormal hormone levels is vulnerable to pulmonary edema, mild upper airway obstruction triggered negative pressure pulmonary. Thus pre-operation hormones supplement is as important as keeping upper airway unobstructed.